The Role of Artificial Intelligence (AI) in Advancing Gender Equality and Women’s Empowerment in Academia: A Conceptual Framework - Karim, Rafidah Abd (European Scientific Journal, ESJ, 2025)
Education has a major impact on a society’s political, social, economic, technological, and human capital development. The history of women’s exclusion from higher education has resulted in a lack of diversity among the highest levels of leadership, particularly at significant institutions. Barriers, including institutional bias, gender preconceptions, and a lack of administrative support, must be overcome by women who aspire to hold leadership positions in higher education. However, AI is an effective tool for promoting gender equality and empowering women around the world through a number of charitable endeavours. The main aim of the study was to present a conceptual framework of AI’s role for gender equality and women’s empowerment in academia. This study used a qualitative and conceptual design of study. A total of 30 identified reviewed articles published between 2015 and 2025 were systematically analysed using thematic analysis to identify the role of AI among women in academia. Three major themes were identified: AI capabilities and tools, empowerment and support mechanisms, and gender equality and institutional impact. A conceptual framework was developed from these findings and shows that these three framework components were connected through a multifaceted, intricate network of interactions and introduced to guide future research that explains the role of AI in advancing gender equality and women’s empowerment in academia. The study serves as a catalyst for creating a more equitable AI landscape. Consequently, this study will promote diversity, which underscores the importance of gender diversity in AI, and can lead to more innovative and well-rounded solutions.